Penyuluhan Teknik Perbanyakan Tanaman Dan Pengendalian Hama Lalat Buah Pada Petani Hortikultura di Kelompok Tani Mapan Sejahtera Kota Tarakan - Rahim, Abdul; Sutrisno, Adi; ., Margiyono (Universitas Tanjungpura, 2019)
The services activity was conducted counseling of plant propagation techniques and control of fruit fly pests on horticultural crops, especially fruit plants. The methods used in the service activities are lectures, discussions, field practice, evaluation, and publication of the results of counseling. The results were showed: (1) increasing farmers' insights on plant propagation techniques, and (2) pest control on horticultural crops, especially fruit flies. The activity had an impact on improving the skills of farmers, especially the propagation techniques of fruit plants. Also, horticultural farmers have alternative business skills that are economically valuable. The farmers also have been the skill to control fruit fly pests, especially in horticultural farmers (fruit planting) groups.